2009
DOI: 10.1108/09513570910966342
|View full text |Cite
|
Sign up to set email alerts
|

New Labour, Network Rail and the third way

Abstract: Purpose -The paper aims to examine the role, funding and status of Network Rail, a very significant example of New Labour's attempt to operationalise the "third way". The analysis of Network Rail is used to critique the "third way" approach to policy-making in Britain. Design/methodology/approach -The paper examines Network Rail, and the significant changes that have occurred since its creation, in the context of the claims originally made for the company by Transport Secretary Byers. It employs critical finan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…She argued that their "contribution has been concerned largely with the reporting changes resulting from privatization … and regulatory issues" ͑Shaoul 1997a, 383͒. To some extent researchers have explored this gap over the last ten years, but there is still little known about the role of accounting within decisions to privatize, the quality of the data that is used to justify the decision, and the way accounting information is used between parties ͑the government, private organizations, and citizens͒ in the development of public policy ͑such as Edwards and Shaoul 2003;Funnell et al 2009;Jupe 2009a͒. Many of these challenge the core claims made by the proponents of neoliberal theory through an exploration of the "realities" that emerged ͑Edwards and Shaoul 2003;Harvey 2005͒. The claim that private ownership leads to the efficient allocation of resources was explored extensively by Martin and Parker ͑1997͒ when they studied 11 newly privatized companies 1 in the U.K. to conclude that the evidence was mixed as would be expected-certainly their research indicated that the reality was far less clear than the theory.…”
Section: Accounting and Privatizationmentioning
confidence: 98%
See 3 more Smart Citations
“…She argued that their "contribution has been concerned largely with the reporting changes resulting from privatization … and regulatory issues" ͑Shaoul 1997a, 383͒. To some extent researchers have explored this gap over the last ten years, but there is still little known about the role of accounting within decisions to privatize, the quality of the data that is used to justify the decision, and the way accounting information is used between parties ͑the government, private organizations, and citizens͒ in the development of public policy ͑such as Edwards and Shaoul 2003;Funnell et al 2009;Jupe 2009a͒. Many of these challenge the core claims made by the proponents of neoliberal theory through an exploration of the "realities" that emerged ͑Edwards and Shaoul 2003;Harvey 2005͒. The claim that private ownership leads to the efficient allocation of resources was explored extensively by Martin and Parker ͑1997͒ when they studied 11 newly privatized companies 1 in the U.K. to conclude that the evidence was mixed as would be expected-certainly their research indicated that the reality was far less clear than the theory.…”
Section: Accounting and Privatizationmentioning
confidence: 98%
“…Although much effort has been mounted to ensure that this view appears natural and self evident ͑with market testing, performance management, public audits, and assessments of risk, see Craig and Amernic ͓2004͔͒, there is now considerable disquiet over its underlying purpose and privatizations' more vested intent ͑Shaoul 1997a; Edwards and Shaoul 2003;Froud 2003;Cahill 2009;Jupe 2009a͒. It is also important to note that the notion of efficiency itself has appeared uncontroversial, but is in fact ambiguous and ill defined ͑Shaoul 1997b; Andrew and Cahill 2009͒. According to Shaoul ͑1997a͒, accounting researchers have contributed little to the analysis of privatization as a policy choice.…”
Section: Accounting and Privatizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, however, there were two very significant concerns which determined the Government's unavoidable response: the company's significant contribution of one fifth of the electricity supply; and concerns should the safety of nuclear power stations be threatened. The Blair Government could have renationalized British Energy in order to remove uncertainty about its future and to secure the electricity supply but, as in the case of Railtrack (Jupe, 2009a), chose not to. Its preference instead was to adopt a complex "third way" approach which relied upon large public subsidy to retain the company in the private sector.…”
Section: Nuclear Liabilities Riskmentioning
confidence: 99%